EVEKTIVITAS PENGGUNAAN APLIKASI CANVA DALAM PEMBELAJARAN BAHASA INDONESIA PADA ASPEK KEMAMPUAN MEMBACA SISWA KELAS V SD INPRES BONTOMANAI KECAMATAN TAMALATE KOTA MAKASSAR - PUTRI PRATIWI (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of using the Canva application in improving the reading skills of fifth-grade students at SD Inpres Bontomanai, Tamalate District, Makassar City. This study was quantitative with a nonequivalent pretest-posttest control group design. The study subjects consisted of 50 students divided into two classes: an experimental class (using Canva) and a control class (not using Canva). Data were collected through pretests and posttests, and analyzed using descriptive statistics and a t-test with a significance level of 0.05. The results showed a significant difference between the posttest scores of the experimental class (mean = 76.80) and the control class (mean = 60.00), with a Sig. (2-tailed) value of 0.000 <0.05. Thus, the use of the Canva application is effective in improving students' reading skills.